Ca2+ Dyshomeostasis Links Risk Factors to Neurodegeneration in Parkinson’s Disease - Xu, Jianjun; Minobe, Etsuko; Kameyama, Masaki (Frontiers in Cellular Neuroscience, 2022)
Parkinson’s disease (PD), a common neurodegenerative disease characterized by motor dysfunction, results from the death of dopaminergic neurons in the substantia nigra pars compacta (SNc). Although the precise causes of PD are still unknown, several risk factors for PD have been determined, including aging, genetic mutations, environmental factors, and gender. Currently, the molecular mechanisms underlying risk factor-related neurodegeneration in PD remain elusive. Endoplasmic reticulum stress, excessive reactive oxygen species production, and impaired autophagy have been implicated in neuronal death in the SNc in PD. Considering that these pathological processes are tightly associated with intracellular Ca2+, it is reasonable to hypothesize that dysregulation of Ca2+ handling may mediate risk factors-related PD pathogenesis. We review the recent findings on how risk factors cause Ca2+ dyshomeostasis and how aberrant Ca2+ handling triggers dopaminergic neurodegeneration in the SNc in PD, thus putting forward the possibility that manipulation of specific Ca2+ handling proteins and subcellular Ca2+ homeostasis may lead to new promising strategies for PD treatment.